Preparation method and application of porous zinc oxide / calcium silicate composite material
Porous zinc oxide/calcium silicate composite materials were prepared by oyster shells and rice husks, and combined with the antibacterial properties of zinc oxide, the problems of insufficient osteogenesis induction, low mechanical strength and insufficient antibacterial properties of traditional bone graft materials were solved, and the biocompatibility, osteoinduction and antibacterial properties of the materials were improved.
Patent Information
- Application Number
- CN202411989356.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Traditional bone graft materials have problems such as insufficient osteogenesis induction, low mechanical strength, mismatch with bone tissue repair rate, and insufficient antibacterial performance. In addition, industrially prepared calcium silicate materials have problems such as limited raw material resources, inability to biodegrade and serious pollution.
Porous zinc oxide/calcium silicate composite materials are prepared by using oyster shells and rice husks, and combined with the antibacterial properties of zinc oxide, materials with good biocompatibility, osteoinductivity, degradability and antibacterial properties are prepared.
The biocompatibility and osteoinductivity of the material are achieved, the proliferation and regeneration ability of bone tissue is improved, and the excellent antibacterial properties are also achieved, solving many defects of traditional materials.
Smart Images

Figure CN119770717A_ABST
Abstract
Description
Technical Field
[0001] The invention provides a preparation method and application of a porous zinc oxide / calcium silicate composite material, belonging to the field of biomedical material bone tissue engineering scaffolds. Background Art
[0002] Every year, more than 2.2 million bone transplants are performed worldwide to repair bone defects, involving the fields of orthopedics, neurosurgery, and stomatology. However, traditional treatment methods have some limitations, such as donor area restrictions, high complication rates, and immune rejection. To this end, there is an urgent need to develop new bone transplant substitutes with good biocompatibility and osteoinductivity. Traditional bioceramic materials include calcium phosphate, calcium sulfate, and hydroxyapatite. Although they have good tissue compatibility and bioactivity, they still have shortcomings such as insufficient osteogenic induction, low mechanical strength, mismatch with bone tissue repair rate, and insufficient antibacterial properties. Compared with traditional calcium-phosphorus materials, calcium silicate-based biomaterials perform better in promoting bone marrow mesenchymal stem cell proliferation, osteogenic differentiation, and bone formation. The presence of calcium in calcium silicate helps promote the formation of calcium-phosphorus layers and the growth of new bones. However, most calcium silicates are currently synthesized from industrial raw materials, which have problems such as limited raw material resources, non-biodegradability, and serious pollution.
[0003] In daily life, a large number of oyster shells are discarded as waste, causing serious environmental pollution. However, the high biological activity of oyster shells gives them potential biological and pharmaceutical application value. Natural oyster shells are composite materials composed of calcium carbonate minerals and biomolecules. The calcium ions and carbonates released by oyster shells can provide a suitable microenvironment for new bone. Trace elements such as magnesium, phosphorus, strontium, and sodium in oyster shells play an important role in promoting angiogenesis and osteogenesis. In addition, the porous structure can provide growth space for new cells and bone tissue. Using discarded oyster shells and rice shells as raw materials to prepare calcium silicate not only reduces dependence on natural resources, realizes the effective utilization of waste, reduces environmental pollution, and conforms to the concept of green and sustainable development, but also has significant advantages in promoting osteogenesis.
[0004] Infection is one of the common complications in bone grafting surgery, which may lead to failure of bone grafting and bone fusion. Therefore, the ideal bone cement should have the ability to promote osteoblast activity and inhibit bacterial growth. Antimicrobial drugs can help to cope with the challenges brought by drug-resistant bacterial infections. Among them, zinc oxide, as a widely used antibacterial material, shows excellent antibacterial effects. By introducing zinc oxide, the antibacterial properties of composite materials can be improved.
[0005] This application uses oyster shells and rice husks to prepare calcium silicate, which not only realizes the recycling of waste and reduces environmental pollution, but also retains various trace elements in oyster shells, such as magnesium, phosphorus, strontium, sodium, etc., which play an important role in promoting angiogenesis and osteogenesis; by adding zinc oxide, the composite material has both bone regeneration promotion performance and excellent antibacterial properties. The zinc oxide / calcium silicate composite material prepared by the present invention provides a feasible and effective new material in the field of bone tissue engineering scaffold materials, which is conducive to the development and development of the field of bone materials. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a porous zinc oxide / calcium silicate composite material. The composite material obtained by the method has good biocompatibility, osteoinductivity, degradability and antibacterial properties, and can better promote the formation of new bone.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for preparing a porous zinc oxide / calcium silicate composite material, comprising the following steps:
[0009] (1) adding ZnO-CaO to an ammonium hydroxide solution to react and obtain a mixed solution; the mixed solution comprises calcium hydroxide, zinc hydroxide and ZnO;
[0010] (2) adding sodium silicate to the mixed solution described in step (1) to react, and obtaining a zinc oxide / calcium silicate composite material after heat treatment of the precipitate.
[0011] In some embodiments, in step (1), the preparation method of ZnO-CaO is: adding the pretreated oyster shell to a Zn(NO3)2 solution for treatment, and drying and calcining the obtained solid in sequence after solid-liquid separation to obtain ZnO-CaO;
[0012] Preferably, the calcination temperature is 700-950° C., and the calcination time is 4-7 hours.
[0013] In some embodiments, the method for pre-treating oyster shells comprises sequentially washing, drying, grinding, and screening the collected oyster shells.
[0014] Preferably, the sieving uses a 800-mesh sieve.
[0015] In some embodiments, in step (1), the mass of the ZnO-CaO is 0.3 g, the concentration of the ammonium hydroxide solution is 0.5 M, and the volume of the ammonium hydroxide solution is 15-20 mL.
[0016] In some embodiments, in step (2), the sodium silicate is prepared by reacting rice husks with a sodium hydroxide solution;
[0017] Preferably, the mass of the rice husk is 0.7 g, the concentration of the sodium hydroxide solution is 2 M, and the volume of the sodium hydroxide solution is 5-10 mL.
[0018] In some embodiments, in step (2), the reaction includes: adding the sodium silicate to the mixed solution of step (1) and stirring, ultrasonicating, and standing to obtain a precipitate.
[0019] In some embodiments, in step (2), the heat treatment comprises: drying the precipitate at 60° C., and then calcining the precipitate at 650-750° C. for 1.5-2.5 h to obtain a zinc oxide / calcium silicate composite material.
[0020] The present invention also provides application of the zinc oxide / calcium silicate composite material prepared by the method in the field of biomedical material bone tissue engineering scaffold.
[0021] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0022] The invention prepares a zinc oxide / calcium silicate composite material by first forming ZnO-CaO, reacting with ammonium hydroxide and then reacting with sodium silicate. The preparation method has mild conditions, fast reaction rate and relatively pure prepared product. The dispersion of Zn in the obtained zinc oxide / calcium silicate composite material is more uniform, and the composite material is rich in pore structure and a large amount of trace elements such as Mg, P, Sr and Na, which is conducive to the proliferation and regeneration of bone tissue.
[0023] Other features and beneficial effects of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other beneficial effects of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The porous scanning electron microscope (SEM) and elemental analysis images of porous zinc oxide / calcium silicate composite materials, where a / b / c are morphology images of porous zinc oxide / calcium silicate composite materials, and d / e / f / g are elemental dispersion images of O / Zn / Ca / Si in the materials, respectively;
[0025] Figure 2 is the X-ray diffraction pattern (XRD) of the porous zinc oxide / calcium silicate composite material;
[0026] Figure 3The picture shows the formation of apatite layer of porous zinc oxide / calcium silicate composite material in human simulated body fluid, where A1 / B1 / C1 / D1 are the morphology of hydroxyapatite (HAp) mineralized layer on the surface of the material after immersion for 1, 3, 5, and 7 days, respectively, and A2 / B2 / C2 / D2 are the elemental composition of hydroxyapatite (HAp) mineralized layer on the surface of the material after immersion for 1, 3, 5, and 7 days, respectively;
[0027] Figure 4 Schematic diagram of the antibacterial effect of porous zinc oxide / calcium silicate composite materials, wherein a and b are the inhibition zone experiments of different materials on Escherichia coli and Staphylococcus aureus, c1 / d1 / e1 are the antibacterial effects of blank samples and different materials on Escherichia coli, c2 / d2 / e2 are the antibacterial effects of blank samples and different materials on Staphylococcus aureus, in the figure, E and E.coli are Escherichia coli, S and S.aureus are Staphylococcus aureus, Control is a blank sample, CS is calcium silicate, and ZnO / CS is a zinc oxide / calcium silicate composite material;
[0028] Figure 5 CT images of porous zinc oxide / calcium silicate composite material repairing rat skull bone, where 4W means 4 weeks, 8W means 8 weeks, Control means blank sample, CS means calcium silicate, and ZnO / CS means zinc oxide / calcium silicate composite material;
[0029] Figure 6 These are the pictures of bone tissue section staining of porous zinc oxide / calcium silicate composite materials for repairing rat skull bones. Among them, 4W means 4 weeks, 8W means 8 weeks, Control means blank sample, CS means calcium silicate, ZnO / CS means zinc oxide / calcium silicate composite material, HE means hematoxylin and eosin method, and Masson means Masson's triple staining method. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a porous zinc oxide / calcium silicate composite material, such as Figure 1 As shown, the following steps are included:
[0031] (1) adding ZnO-CaO to an ammonium hydroxide solution to react and obtain a mixed solution; the mixed solution comprises calcium hydroxide, zinc hydroxide and ZnO;
[0032] Specifically, 0.3 g of ZnO-CaO is added to a 15-20 mL ammonium hydroxide solution with a concentration of 0.5 M, and the mixture is stirred vigorously to obtain a mixed solution including calcium hydroxide, zinc hydroxide and ZnO;
[0033] It should be noted that the present invention needs to strictly control the amount of ammonium hydroxide used to prevent it from being excessive and causing unnecessary complex reaction with zinc oxide to form unnecessary amino zinc complex, which wastes zinc source and affects product purity.
[0034] In a preferred embodiment, the present invention adds 30 g of pretreated oyster shells to 500 mL of a 0.05 M Zn(NO3)2 solution and stirs for 12 h. After solid-liquid separation, the solid is placed in an oven at 60°C for drying, and then placed in a muffle furnace and calcined at 900°C for 5 h to obtain ZnO-CaO.
[0035] Preferably, the present invention soaks the collected oyster shells in deionized water at room temperature for 2 hours, removes residual garbage on the surface and then washes them with deionized water, then puts them in a vacuum drying oven at 60° C. and dries them for 6 hours, takes them out, grinds them into powder, and then passes them through an 800-mesh sieve to obtain pretreated oyster shells;
[0036] (2) adding sodium silicate to the mixed solution described in step (1) to react, and obtaining a zinc oxide / calcium silicate composite material after heat treatment of the precipitate.
[0037] Specifically, the sodium silicate is added to the mixed solution of step (1) and stirred for 30 minutes, then ultrasonicated for 30 minutes and allowed to stand to obtain a precipitate, the precipitate is dried at 60° C., and then calcined at 650-750° C. for 1.5-2.5 hours to obtain a zinc oxide / calcium silicate composite material;
[0038] It should be noted that the zinc cations in the mixed solution can act as a catalyst in the multiphase reaction, reducing the activation energy of the solid phase reaction. At the same time, the zinc cations can form coordination complexes with other reactants (such as calcium hydroxide or sodium silicate), changing the reaction path and the energy of the transition state, thereby accelerating the reaction rate.
[0039] In a preferred embodiment, the present invention prepares sodium silicate by reacting 0.7 g of rice husk with 5 mL of a 2M sodium hydroxide solution.
[0040] It should be noted that the present application first prepares ZnO-CaO, and then reacts the substance with ammonium hydroxide, and then reacts with sodium silicate to prepare zinc oxide / calcium silicate, rather than directly calcining CaCO3 into CaO, and then calcining with silicon dioxide to obtain CaSiO3, and then adding a zinc source and calcining to prepare zinc oxide / calcium silicate because the experiment found that when using a high-temperature calcination method to prepare calcium silicate, CaO and SiO2 react at a high temperature of 1250-1300 ° C, and at this temperature, not only calcium silicate will be generated, but also dicalcium silicate and tricalcium silicate and other variants will be obtained; even if the reactants are mixed with the aid of a ball mill, CaO and SiO2 cannot react completely, and there will be residual CaO and SiO2 in the product, so the purity of the calcium silicate obtained by this method is not high, and the product is still impure after the subsequent introduction of the zinc source. Moreover, because the zinc source is added after the calcium silicate is formed, this will cause uneven distribution of the zinc element in the material, affecting the performance of the material.
[0041] The present invention also provides application of the zinc oxide / calcium silicate composite material prepared by the method in the field of biomedical material bone tissue engineering scaffold.
[0042] Specifically, the present invention uses SD rats as experimental subjects to evaluate the ability of calcium silicate (CS) and zinc oxide / calcium silicate (ZnO-CS) nanocomposites to promote bone tissue regeneration. The specific implementation method is: 24 male Sprague-Dawley (SD) rats aged 8 weeks and weighing 250±25g were selected, and the rats were divided into three groups using a random number table method; a symmetrical defect hole with a diameter of 5mm was drilled in the center of the skull of each rat with a drill, one of which was a blank control group, and the defect was not filled with material, and the other two experimental groups were filled with CS materials and ZnO-CS materials sterilized by ultraviolet light, respectively; at 4 weeks and 8 weeks, four rats in each group were killed, the skull was dissected, the bones were separated from the surrounding muscles and fascia, and then the samples were immersed in a 4% paraformaldehyde solution for overnight fixation, and then the samples were scanned using a CT machine to evaluate the formation of new bone in the defect area. After CT examination, the skull of SD rats was decalcified with formic acid decalcification solution for 48 hours, and then rinsed with running water for 24 hours; the tissue was embedded in paraffin after gradient dehydration with ethanol solution, cut into 4μm slices, and then rinsed with xylene and ethanol; finally, the slices were treated with hematoxylin and eosin (HE), and some slices were stained with Masson's triple staining method. The results of the stained slices were recorded with an optical microscope, and the formation of new bone tissue and various inflammatory indicators were evaluated under the microscope by using histological staining.
[0043] In addition, the present invention uses SBF solution to simulate the formation of apatite layer in vivo, and detects the formation of apatite on the surface of the material by SEM scanning and semi-quantitative analysis of the apatite layer on the surface of the material at different cycles, thereby reflecting the material's ability to promote bone formation. The specific implementation method is: the prepared zinc oxide / calcium silicate composite material is immersed in a human simulated body fluid (SBF) solution and incubated at 37°C static conditions for 1, 3, 5 and 7 days; after each stage, the sample is taken out of the solution, washed with deionized water and dried in a 50°C oven, and finally the formation of the apatite layer is observed using a scanning electron microscope.
[0044] The present invention also uses the antibacterial zone method and the bacterial counting method to evaluate the antibacterial ability of the composite material against Escherichia coli and Staphylococcus aureus. The specific implementation method is as follows: 1) Take the diluted Escherichia coli and Staphylococcus aureus liquid and react with CS and ZnO-CS for 30 minutes respectively; 2) Prepare an agar solution and sterilize it in an autoclave, then pour the sterilized agar solution into a sterile culture dish and wait for it to solidify; 3) Dilute Escherichia coli and Staphylococcus aureus, then inoculate the two bacteria on the agar plate respectively, finally seal the culture dish, incubate it in a 37°C constant temperature incubator for 18 hours, then count the number of bacteria and take photos for analysis.
[0045] The present invention is further described in detail in conjunction with specific embodiments. The following embodiments can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.
[0046] Example:
[0047] (1) Oyster shell pretreatment: Collect discarded oyster shells (rich in CaCO3), soak the collected oyster shells in deionized water at room temperature for 2 hours, and use tweezers to tear off the residual garbage on the surface from the oyster shells. After repeated cleaning, put them in a vacuum drying oven at 60°C for 6 hours, take them out, grind them into powder in an agate mortar, and pass them through an 800-mesh sieve.
[0048] (2) Preparation of ZnO-CaO: Take 30 g of the oyster shell powder obtained in step (1), add it to 500 mL of 0.05 M Zn(NO3)2 solution, use a magnetic stirrer to continuously stir and soak for 12 h, separate the mixture into solid and liquid, discard the supernatant and place it in an oven to dry at 60°C, then place it in a muffle furnace and set the calcination conditions to 900°C. After calcination for 5 h, ZnO-CaO is obtained.
[0049] (3) Preparation of a mixed solution: 0.3 g of ZnO-CaO prepared in step (2) was added to 20 mL of 0.5 M ammonium hydroxide solution to obtain a mixed solution.
[0050] (4) Preparation of sodium silicate solution: 0.7 g of rice husk (rich in nano-SiO2) was reacted with 5 mL of 2M sodium hydroxide solution to obtain a sodium silicate solution.
[0051] (5) Preparation of zinc oxide / calcium silicate: The sodium silicate prepared in step (4) was added to the mixed solution prepared in step (3), and stirred for 30 min. The mixture was ultrasonicated for 30 min, and allowed to stand to obtain a precipitate. The precipitate was then dried at 60° C. and calcined at 700° C. for 2 h to obtain a zinc oxide / calcium silicate composite material.
[0052] Comparative Example:
[0053] (1) Oyster shell pretreatment: Collect discarded oyster shells (rich in CaCO3), soak the collected oyster shells in deionized water at room temperature for 2 hours, and use tweezers to tear off the residual garbage on the surface from the oyster shells. After repeated cleaning, put them in a vacuum drying oven at 60°C for 6 hours, take them out, grind them into powder in an agate mortar, and pass them through an 800-mesh sieve.
[0054] (2) Preparation of CaO: The oyster shell powder obtained in step (1) was placed in a muffle furnace and calcined at 900° C. for 5 h to obtain CaO.
[0055] (3) Preparation of calcium hydroxide solution: 0.3 g of CaO in step (2) was added into 20 mL of 0.5 M ammonium hydroxide solution to obtain a calcium hydroxide solution.
[0056] (4) Preparation of sodium silicate solution: 0.7 g of rice husk (rich in nano-SiO2) was reacted with 5 mL of 2M sodium hydroxide solution to obtain a sodium silicate solution.
[0057] (5) Preparation of calcium silicate: The sodium silicate prepared in step (4) is added to the calcium hydroxide solution prepared in step (3), stirred for 30 min, ultrasonicated for 30 min, and then allowed to stand to obtain a precipitate. The precipitate is then dried at 60° C. and calcined at 700° C. for 2 h to obtain calcium silicate.
[0058] The zinc oxide / calcium silicate composite material prepared by the method of the present invention has a porous structure (specific surface area of 23.61m 2 / g, and the total adsorption pore volume is 0.072cm 3 / g)( Figure 1 ), XRD test results ( Figure 2 ) shows obvious diffraction peaks of calcium silicate, but the diffraction peaks of zinc oxide are not obvious, which is related to the small amount of zinc oxide. Combining the XRD test results with the SEM test results confirms the successful preparation of the zinc oxide / calcium silicate composite material.
[0059] In addition, the porous zinc oxide / calcium silicate composite material prepared by the method of the present invention has a highly interconnected pore network, and its pore size and porosity are more suitable for cell penetration and vascularization. Compared with ordinary commercial calcium silicate, it is beneficial to accelerate the bone regeneration process; the material also has good biocompatibility and osteoconductivity, can promote cell attachment, proliferation and differentiation, and can more effectively guide new bone formation compared with some commercial materials; by optimizing the preparation process, the porous zinc oxide / calcium silicate composite material can provide a more cost-effective solution while ensuring performance to meet a wider range of clinical needs.
[0060] Performance Testing:
[0061] The performance tests were performed on the embodiments and comparative examples, and the test contents and methods were as follows:
[0062] (1) The mineralization of apatite on the surface of porous zinc oxide / calcium silicate composites in SBF was observed using SEM: the prepared calcium silicate or zinc oxide / calcium silicate composites were immersed in simulated body fluid (SBF) solution and incubated at 37°C under static conditions for 1, 3, 5 and 7 days; after each stage, the samples were taken out of the solution, washed with deionized water and dried in an oven at 50°C, and finally the formation of the apatite layer was observed using a scanning electron microscope.
[0063] The results are as follows Figure 3 As shown in the figure, on the first day of immersion, sporadic hydroxyapatite (HAp) mineralization layers appeared on the surface of the material, mostly in the form of small particles and corals. After 5 days of immersion, the surface of the sample was covered with a spherical apatite layer, and the apatite layer deposition was more obvious. On the 7th day of immersion, the field of view was completely filled with spherical HAp. The HAp formed self-aggregates with a lychee-shaped and burr-like surface and a diameter of about 1 μm. This phenomenon may be due to the fact that the release rate of calcium ions during immersion is faster than that of silicon ions, resulting in the formation of a silicon-rich layer on the surface of calcium silicate. In addition, semi-quantitative analysis of elements showed that the content of P element increased with the increase of immersion days, indicating that the formed hydroxyapatite layer became denser with the increase of time. This shows that zinc oxide / calcium silicate has good in vitro bioactivity and is very beneficial for bone tissue repair.
[0064] (2) The antibacterial effect of zinc oxide / calcium silicate materials was evaluated by measuring the diameter of the inhibition zone and the inhibition rate: 1) The diluted Escherichia coli and Staphylococcus aureus solutions were reacted with calcium silicate and zinc oxide / calcium silicate for 30 min respectively; 2) An agar solution was prepared and sterilized in an autoclave, and then the sterilized agar solution was poured into a sterile culture dish and allowed to solidify; 3) Escherichia coli and Staphylococcus aureus were diluted, and then the two bacteria were inoculated onto the agar plate respectively. Finally, the culture dish was sealed and incubated in a constant temperature incubator at 37°C for 18 h, and then the number of bacteria was counted and photographed for analysis.
[0065] The results are as follows Figure 4 As shown, the radius of the inhibition zone of calcium silicate without zinc oxide is only 0.1-0.3cm, and the antibacterial effect is weak. This antibacterial property may be related to the weak alkaline environment caused by the dissolution of calcium silicate. In contrast, the inhibition zone radius (0.5-0.7cm) of zinc oxide / calcium silicate against Escherichia coli and Staphylococcus aureus increased significantly. Therefore, the composite material has a significant antibacterial effect on both Escherichia coli and Staphylococcus aureus, and the antibacterial property is better than that of calcium silicate. In addition, according to the results of the plate count method, calcium silicate itself has a partial antibacterial effect due to being in an alkaline environment, but the antibacterial effect is not significant. On the other hand, due to the presence of zinc oxide, zinc oxide / calcium silicate reaches 98% against Staphylococcus aureus and 99% against Escherichia coli. The excellent antibacterial properties of zinc oxide / calcium silicate are verified.
[0066] (3) Repair of skull defects in SD rats: Twenty-four male Sprague-Dawley (SD) rats aged 8 weeks and weighing 250±25 g were selected and divided into three groups using a random number table. A symmetrical defect with a diameter of 5 mm was drilled in the center of the skull of each rat using a drill. One group was a blank control group, in which the defect was not filled with material. The other two experimental groups were filled with calcium silicate material sterilized by ultraviolet light and zinc oxide / calcium silicate material, respectively. At 4 and 8 weeks, four rats in each group were killed, the skulls were dissected, the bones were separated from the surrounding muscles and fascia, and the samples were then immersed in 4% paraformaldehyde solution for overnight fixation. Subsequently, the samples were scanned using a CT machine to evaluate the formation of new bone in the defect area. After CT examination, the skull of SD rats was decalcified with formic acid decalcification solution for 48 hours, and then rinsed with running water for 24 hours; the tissue was embedded in paraffin after gradient dehydration with ethanol solution, cut into 4μm slices, and then rinsed with xylene and ethanol; finally, the slices were treated with hematoxylin and eosin (HE), and some slices were stained with Masson's triple staining method (Masson), and the results of the stained slices were recorded with an optical microscope. The formation of new bone tissue and various inflammatory indicators were evaluated under the microscope by using histological staining.
[0067] CT results ( Figure 5 ) showed that as time went by, more new bone tissue grew in, and at the same time, the repair effect of zinc oxide / calcium silicate material was better than that of calcium silicate.
[0068] The formation of new bone tissue was observed by using histological staining and other methods. Figure 6As shown in the figure, at 4 weeks, there was only some fibrous connective tissue in the defect of the blank group, and basically no new bone tissue was formed. At 8 weeks, fibrous connective tissue was generated in the defect, and some new bone tissue was formed. For the calcium silicate group, at 4 weeks, the defect was filled with implant materials wrapped with fibrous connective tissue, the implant material was not completely degraded, and a small number of phagocytes and multinuclear giant cells were seen in the implant material. New cells and some blood vessels were observed in the defect at 8 weeks. In the zinc oxide / calcium silicate group, the repair effect was better due to the incorporation of zinc oxide material. At 8 weeks, a large number of phagocytes and multinuclear giant cells were seen in the implant material, and tumor bone formation and angiogenesis were seen in the defect. The zinc oxide / calcium silicate group performed best in new bone tissue formation and angiogenesis. The histological section results of animal experiments proved that zinc oxide / calcium silicate has excellent ability to promote bone tissue regeneration.
[0069] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.
Claims
1. A method for preparing a porous zinc oxide / calcium silicate composite material, characterized in that: The following steps are involved: (1) adding ZnO-CaO to an ammonium hydroxide solution to react and obtain a mixed solution; the mixed solution comprises calcium hydroxide, zinc hydroxide and ZnO; (2) adding sodium silicate to the mixed solution described in step (1) to react, and obtaining a zinc oxide / calcium silicate composite material after heat treatment of the precipitate.
2. The method for preparing the porous zinc oxide / calcium silicate composite material according to claim 1, characterized in that: The method for preparing the ZnO-CaO in step (1) is as follows: adding the pretreated oyster shells to a Zn(NO3)2 solution for treatment, and after solid-liquid separation, drying and calcining the obtained solid in sequence to obtain ZnO-CaO.
3. The method for preparing the porous zinc oxide / calcium silicate composite material according to claim 2, characterized in that: The calcination temperature is 700-950° C., and the calcination time is 4-7 hours.
4. The method for preparing the porous zinc oxide / calcium silicate composite material according to claim 2, characterized in that: The method for obtaining pre-treated oyster shells comprises sequentially washing, drying, grinding and screening the collected oyster shells.
5. The method for preparing the porous zinc oxide / calcium silicate composite material according to claim 4, characterized in that: The sieving was performed using a 800-mesh sieve.
6. The method for preparing the porous zinc oxide / calcium silicate composite material according to claim 1, characterized in that: The mass of the ZnO-CaO in step (1) is 0.3 g, the concentration of the ammonium hydroxide solution is 0.5 M, and the volume of the ammonium hydroxide solution is 15-20 mL.
7. The method for preparing the porous zinc oxide / calcium silicate composite material according to claim 1, characterized in that: The sodium silicate described in step (2) is prepared by reacting rice husk with sodium hydroxide solution; The mass of the rice husk is 0.7 g, the concentration of the sodium hydroxide solution is 2 M, and the volume of the sodium hydroxide solution is 5-10 mL.
8. The method for preparing the porous zinc oxide / calcium silicate composite material according to claim 1, characterized in that: The reaction described in step (2) comprises: adding the sodium silicate to the mixed solution described in step (1), stirring, ultrasonicating, and standing to obtain a precipitate.
9. The method for preparing the porous zinc oxide / calcium silicate composite material according to claim 1, characterized in that: The heat treatment in step (2) comprises: drying the precipitate at 60° C., and then calcining the precipitate at 650-750° C. for 1.5-2.5 hours to obtain a zinc oxide / calcium silicate composite material.
10. Use of the zinc oxide / calcium silicate composite material prepared according to the method according to any one of claims 1 to 9 in the field of biomedical materials and bone tissue engineering scaffolds.